#TITLE_ALTERNATIVE# - (NIM 20506037), RAHMAWATI
The concept of redox is one of difficult chemical materials must be understood by students, because this matery abstract. There should be an alternative learning model to minimize the student difficulties in remembering it. The model used a laboratory (Laboratory Based Learning). To predict the order of oxidizing capacities of K2Cr2O7, KMnO4 and KBrO3 (with the same concentration ~ 0.1 N) to Fe2+ ion in Mohr salt 0,1 M and to Sn2+ ion in SnCI2.2H2O salt 0,05 M, had been used to the redox titrimetry. This research was done to develop an experiment module that can help students to understand the redox concept in many cases, such as : the order of oxidizing capacities of some oxidators to Fe2+ ion and Sn2+ ion, predict redox reaction and potential force of MnO4-, Cr2O72-, BrO3-, Fe2+ and Sn2+ ions. In this research, the determination of Fe2+ in Mohr salt, (NH4)2SO4.FeSO4.6H2O, and Sn2+ in tin(II)chloride salt, SnCI2.2H2O, were based on the volume of titrant (oxidator) used in the titrimetry. From result of the titration is obtained by redox titration curve each oxidator with grooving number of titrant volumes (oxidator) to Esel, so we could predict oxidation capacity from all three oxidators based on the value of equivalent point obtained at each redox titration curve. Based on the result of research of redox titration of salt Mohr with oxidator K2Cr2O7, KMnO4 and KBrO3 is obtained the value of equivalent point successively 1073,5 mV, 1249,6 mV and 1235,4 mV while at redox titration of salt SnCl2.2H2O with oxidator K2Cr2O7, KMnO4 and KBrO3 is obtained the value of equivalent successively 874,2 mV, 1131,7 mV and 1015,8 mV. Based on the research, KMnO4 was a stronger oxidator than KBrO3 and K2Cr2O7, Sn2+ ion was a stronger reductor than Fe2+ ion. Thus the order from the strongest oxidator to the weakest was MnO4- > BrO3- > Cr2O72- > Fe2+ > Sn2+. The result of this research will be written in the experiment module to help teacher develop learning method. This experiment module was useable to learn the other material (cross matery), to help raise students motivation in mastering the concept of redox and electrochemical, and to help students remember the basic concept of redox reaction based on their laboratory work (Laboratory Based-Learning).